Developmental Trajectories of Restricted and Repetitive Behaviors and Interests in Children with Autism Spectrum Disorders - Richler, Jennifer (2010)
This study examined how restricted and repetitive behaviors and interests (RRBs) developed over time in a sample of children with Autism Spectrum Disorders (ASD). One-hundred ninety-two children referred for a diagnosis of autism at age 2 and 22 children with nonspectrum development disorders were evaluated with a battery of cognitive and diagnostic measures at age 2 and subsequently at ages 3, 5, and 9. Factor analysis of the RRB items on the Autism Diagnostic Interview – Revised revealed two RRB factors at each wave of data collection, one comprised of ‘repetitive sensorimotor’ (RSM) behaviors and the other of ‘insistence on sameness’ (IS) behaviors. For children with ASD, RSM scores remained relatively high over time, indicating consistent severity, whereas IS scores started low and increased over time, indicating worsening. Having a higher NVIQ at age 2 was associated with milder concurrent RSM behaviors and with improvement in these behaviors over time. There was no relationship between NVIQ at age 2 and IS behaviors. However, milder social/communicative impairment, at age 2 was associated with more severe concurrent IS behaviors. Trajectory analysis revealed considerable heterogeneity in patterns of change over time for both kinds of behaviors. These findings are discussed in terms of their implications for our understanding of RRBs in ASD and other disorders, making prognoses about how RRBs will develop in children with ASD as they get older, and using RRBs to identify ASD phenotypes in genetic studies.